2013
DOI: 10.1063/1.4793701
|View full text |Cite
|
Sign up to set email alerts
|

On the levitation force in horizontal core-annular flow with a large viscosity ratio and small density ratio

Abstract: A numerical study has been made of horizontal core-annular flow: the flow of a high-viscosity liquid core surrounded by a low-viscosity liquid annular layer through a horizontal pipe. Special attention is paid to the question how the buoyancy force on the core, caused by a density difference between the core and the annular layer, is counterbalanced. The volume-of-fluid method is used to calculate the velocities and pressures in the two liquids. At the start of the calculation the core is in a concentric posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 16 publications
(23 reference statements)
1
30
0
Order By: Relevance
“…The wave evolution presented high wave amplitude which the core was destabilized forming a structure of OSTW. The initial formation of waves at the pipe top with the smooth interface at the bottom has been reported by Ooms et al, where the oil velocity is U o = U w with a high viscosity of µ o = 0.601 Pa · s and oil core density of ρ o = 980 kg · m −3 . The high wave amplitude and short wavelength were found in theoretical and experimental studies by Joseph et al and Sotgia et al using water input fractions between C w = 0.2 and C w = 0.06, respectively.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The wave evolution presented high wave amplitude which the core was destabilized forming a structure of OSTW. The initial formation of waves at the pipe top with the smooth interface at the bottom has been reported by Ooms et al, where the oil velocity is U o = U w with a high viscosity of µ o = 0.601 Pa · s and oil core density of ρ o = 980 kg · m −3 . The high wave amplitude and short wavelength were found in theoretical and experimental studies by Joseph et al and Sotgia et al using water input fractions between C w = 0.2 and C w = 0.06, respectively.…”
Section: Resultsmentioning
confidence: 54%
“…An extensive study of mathematical modelling has been used with an empirical input interface structure assuming a shape of the wave such as: sawtooth wave, snake waves, and smooth interface with a concentric solid core. Computational fluid dynamics have been applied to calculate the turbulent annular flow using the k‐ϵ model with laminar viscous oil, and for two‐phase modelling .…”
Section: Introductionmentioning
confidence: 99%
“…As shown by Ooms et al 5 the waves can generate a downward force (due to a pressure buildup at the top of the pipe) that counterbalances the upward buoyancy force in horizontal core-annular flow in case of a smaller density of the core liquid than the density of the annular liquid, thus making a stationary flow possible. In that case, the core will get an eccentric position in the pipe due to the buoyancy force and the waves will become less symmetric in the longitudinal direction of the pipe and also nonaxisymmetric (for more details see Ooms et al 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found the same result. The details of this study are reported in Ooms et al 5 We have extended this calculation by studying the influence of the initial conditions by changing these conditions while keeping the physical parameters, the computational mesh, and the time step restriction the same as in the foregoing calculation. We studied two different initial conditions.…”
Section: Validation Against Linear Stability Calculationsmentioning
confidence: 99%
See 1 more Smart Citation